Use of extracorporeal membrane oxygenation in cystic fibrosis in an Australian cystic fibrosis centre. Issue 3 (6th March 2018) - Sivam, Sheila; Dentice, Ruth; Reddy, Nazmeen; Moriarty, Carmel; Yozghatlian, Veronica; Mellis, Craig; Torzillo, Paul; Glanville, Allan; Gattas, David; Bye, Peter
Abstract: Extracorporeal membrane oxygenation (ECMO) support is used in selected patients with cystic fibrosis (CF) as a bridge to transplantation. Our aim was to describe briefly treatment and outcomes of six CF patients who received ECMO. One patient received a lung transplant and another recovered from acute respiratory failure. Four died despite ECMO support. Lack of timely availability of suitable donor lungs and patient selection are contributing factors.